Assessment of Effectiveness of Seasonal Influenza Vaccination During Pregnancy in Preventing Influenza Infection in Infants in England, 2013–2014 and 2014–2015. (9th November 2019) - Walker, Jemma L; Zhao, Hongxin; Dabrera, Gavin; Andrews, Nick; Thomas, Sarah L; Tsang, Camille; Ellis, Joanna; Donati, Matthew; Pebody, Richard G
Abstract: Maternal influenza vaccination is increasingly recognized to protect infants from influenza infection in their first 6 months. We used the screening method to estimate vaccine effectiveness (VE) against laboratory-confirmed influenza in infants in England, using newly available uptake data from the Clinical Practice Research Datalink pregnancy register, matched on week of birth and region and adjusted for ethnicity. We found VE of 66% (95% confidence interval [CI], 18%–84%) in the 2013–2014 season and 50% (95% CI, 11%–72%) in 2014–2015, with similar VE against influenza-related hospitalization. VE against the dominant circulating influenza strain was higher, at 78% (95% CI, 16%–94%) against H1N1 in 2013–2014, and 60% (95% CI, 16%–81%) against H3N2 in 2014–2015. Abstract : We show that maternal influenza vaccination provides significant protection for infants in the first 6 months of life against influenza-related hospitalization in both the A(H1N1)pdm09– and A(H3N2)–dominated seasons.